ENCOURAGING STUDENTS TO WRITE A PARAGRAPH BY USING SEMANTIC MAPPING STRATEGY - Sulistyo, Teguh; Ningsih, M.G. Sri (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2013)
Of four English language skills, writing is considered the most difficult skill which must be mastered by Indonesian students since it is a very complex process that drives students to explore their thoughts, experiences, schemata, and ideas. Due to the problems faced by the students of Kanjuruhan University in creating ideas related to the topic and construct the ideas into a good unity of a paragraph, this study was conducted to facilitate the students to compose a descriptive paragraph. The findings of the research, taken at Kanjuruhan University of Malang, proved that Semantic Mapping strategy was valuable to increase the studentsâ writing skills.Keywords: semantic mapping strategy, descriptive paragraph